Smart Quarantine vs Strict Lockdown: Restrictions on Political Rights in Anti-Pandemic Strategies in the Czech Republic - Skrzypek, Maciej Filip (Routledge, 2024)
This chapter aims to trace the evolution of the state authorities’ attitude to restrict fundamental political rights in the Czech Republic during the coronavirus pandemic from 11 March 2020 to the end of March 2021. At that time, the Czech authorities changed the anti-pandemic strategy, which impacted certain rights and freedoms. During “a second wave”, the ruling elites decided to replace smart quarantine with a strict lockdown through an extra-constitutional state of emergency since February 2021. These changes aimed to extend the government's scope of power and allowed ignoring parliamentary opposition. The shift in strategy led to an intensification of the implementation of quasi-militant democracy instruments, which decreased the political nation's independence. Therefore, the author will address the motivations and results of anti-pandemic policy changes that impact the discussed sovereignty. That reflection is crucial for debate on implementing anti-democratic measures as part of the policy to deal with the subsequent widespread epidemics and other crises. In this chapter, the author refers to interdisciplinary studies on the effectiveness of pandemic strategies in the country, which, together with analysing the restriction of political rights, will provide answers to the legitimacy of changing the proposed action in the second half of 2020. The periodisation of the first year of the coronavirus crisis is presented in the diagram below.